Development of matzo made of wholemeal rye flour and its implementation in the industry - Zakupszki Zita Boglárka; Véha Antal; Szabó P. Balázs (2018)
In the baking industry, continuous development of products is required because consumers with different nutritional needs are pushing for new requirements for food. Along with the low caloric content, there is growing attention to the functional effects of foods. The aim of our work is the development of a matzo made of wholemeal rye flour, which helps in healthy nutrition for the customer’s and more economical from production’s point of view. The main aim of the product development in our project is to increase the nutrient content by the raise of mineral and fibre content. In the first part of our work we performed basic measurements with flours used during product development. We measured the quantity and quality of gluten protein with Glutomatic-Gluten Index System, the activity of amylase enzymes with Falling Number 1400 and we did complex dough monitoring with METEFÉM Valorigraphe FQA 205. In the second part of our project we compare the basic matzo with matzos made of 3 different recipes. Based on results of examinations it can be ascertain that the Sample 2 shows more advantageous values of the fibre content’s and the prime cost’s point of view.